PROFITABILITAS PERBANKAN SYARIAH - Kun Ismawati; Nurhayati2 . (Universitas Sahid Surakarta, 2014)
This studyaimed toanalyze theeffect ofSize, Total Equity to Total Assets, Total Loans to Total Assets, Total Deposits to Total Assets on ROA(Return on Assets) onBankSyariahIn Indonesia. Purposive sampling method used in this research study. There were two syariah banks in this research. The research samples werein the form ofsecondary data. The data was listedinthe Indonesia Stock Exchangeduring period2009-2013. The statistical method usedtotest the hypothesisin this study was multiple regression. The results of the data analysis obtained in this study were: 1) Size has a positive but not significant effect to the profitability of Syaria banks 2) Total Equity To Total Assets(TE / TA) has a positive but not significant effect on profitability. 3) Total Loans to Total Assets (TL / TA) has a negative but not significant effect on profitability. 4) Total Deposits To Total Assets (TD / TA) has a positive but not significant effect on profitability